2019
DOI: 10.1002/1878-0261.12602
|View full text |Cite
|
Sign up to set email alerts
|

RNA‐sequence‐based microRNA expression signature in breast cancer: tumor‐suppressive miR‐101‐5p regulates molecular pathogenesis

Abstract: Aberrantly expressed microRNA (miRNA) are known to disrupt intracellular RNA networks in cancer cells. Exploring miRNA-dependent molecular networks is a major challenge in cancer research. In this study, we performed RNA-sequencing of breast cancer (BrCa) clinical specimens to identify tumor-suppressive miRNA in BrCa. In total, 64 miRNA were identified as candidate tumor-suppressive miRNA in BrCa cells. Analysis of our BrCa signature revealed that several miRNA duplexes (guide strand/passenger strand) derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
69
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 60 publications
(122 reference statements)
3
69
0
Order By: Relevance
“…Firstly, we evaluated miR-99a-5p expression in tissue samples from 26 healthy patients and 103 BC patients. The downregulation of miR-99a-5p in BC tissue was confirmed, in agreement with previous studies [ 23 , 24 , 25 , 26 ]. Besides, our result was also validated in the TCGA cohort.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Firstly, we evaluated miR-99a-5p expression in tissue samples from 26 healthy patients and 103 BC patients. The downregulation of miR-99a-5p in BC tissue was confirmed, in agreement with previous studies [ 23 , 24 , 25 , 26 ]. Besides, our result was also validated in the TCGA cohort.…”
Section: Discussionsupporting
confidence: 92%
“…Several authors assessed miR-99a expression in BC tissues and demonstrated its downregulation when compared to healthy tissues [ 23 , 24 , 25 , 26 ]. In this respect, miR-99a has been confirmed to be a tumour suppressor and its overexpression was associated with proliferation, invasion, and migration inhibition in BC cells in vitro and in vivo [ 23 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously determined miRNA expression signatures in various types of cancers using RNA sequencing [ 15 , 16 , 17 , 18 , 19 ]. Our recent studies have demonstrated that some passenger strands derived from pre-miRNAs contribute to the malignant transformation of cancer cells [ 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously determined miRNA expression signatures in various types of cancers using RNA sequencing [ 15 , 16 , 17 , 18 , 19 ]. Our recent studies have demonstrated that some passenger strands derived from pre-miRNAs contribute to the malignant transformation of cancer cells [ 15 , 16 , 17 , 18 , 19 ]. We have shown that both strands of miRNAs (e.g., pre- miR-144 , pre- miR-145 and pre- miR-150 ) were significantly downregulated in lung cancer tissues, and their ectopic expression attenuated the malignant phenotypes of lung cancer cells (e.g., cancer cell proliferation, migration and invasion) [ 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%